Working in “NK Mode”: Natural Killer Group 2 Member D and Natural Cytotoxicity Receptors in Stress-Surveillance by γδ T Cells - Silva-Santos, Bruno; Strid, Jessica (Frontiers in Immunology, 2018)
Natural Killer cell Receptors (NKRs) are germline-encoded transmembrane proteins that regulate the activation and homeostasis of NK cells as well as other lymphocytes. For γδ T cells, NKRs play critical roles in discriminating stressed (transformed or infected) cells from their healthy counterparts, as proposed in the ‘lymphoid stress-surveillance’ theory. Whereas the main physiologic role is seemingly fulfilled by NKG2D, constitutively expressed by γδ T cells, enhancement of their therapeutic potential may rely on Natural Cytotoxicity Receptors (NCRs), like NKp30 or NKp44, that can be induced selectively on human Vδ1+ T cells. Here we review the contributions of NCRs, NKG2D and their multiple ligands, to γδ T cell biology in mouse and human.